Pendekatan RAD Dalam Perancangan GIS Penyebaran Penyakit (Studi Kasus: Puskesmas Kaligangsa Brebes) - Husni Faqih; Tika Dian Avisha (Indonesian Journal on Software Engineering (IJSE), 2017)
Abstract - Information technology can be accessed indefinitely and time. Kaligangsa Wetan Health Center in Brebes Sub-district is a party related to the health service and the community. The absence of a container to provide information directly to monitor the spread of information and the number of incoming patient data requires considerable time, in data processing and information handling patient so very slowly makes less effective and efficient. Geographic information system (GIS) disease spread across 6 sub-district health centers that serve kaligangsa wetan This system will accelerate staff performance to be faster, precise and accurate so as to make efficiency better.To overcome this problem, the puskesmas requires a new computerized information system. Data collection methods carried out were observation, interviews and literature. The system development approach used is the Rapid Application Development (RAD) method. This study resulted in a system design of geographical information system for the spread of disease at health centers in the region of Wetan, Brebes. Keywords: Geographic Information System, Rapid Application Development (RAD)